Market Design and Moral Behavior - Michael Kirchler; Jürgen Huber; Matthias Stefan; Matthias Sutter (Institute for the Study of Labor (IZA), 2015)
In an experiment with 739 subjects we study whether and how different interventions might have an influence on the degree of moral behavior when subjects make decisions that can generate negative externalities on uninvolved parties. Particularly, subjects can either take money for themselves or donate it to UNICEF for measles vaccines. By considering two fairly different institutional regimes one with individual decision making, one with a double-auction market we expose the different interventions to a kind of robustness check. We find that the threat of monetary punishment promotes moral behavior in both regimes. Getting subjects more involved with the traded good has no effect, though, in both regimes. Only the removal of anonymity, thus making subjects identifiable, has different effects across regimes, which we explain by different perceptions of responsibility.
Keywords: C91; C92; D47; 330; morals; market design; experiment